Public Sector Collective Bargaining in Canada: Beginning of the End or End of the Beginning - Ponak, Allen (Relations industrielles / Industrial Relations, 1996)
The article reviews the book, "100 Public Sector Collective Bargaining in Canada: Beginning of the End or End of the Beginning," by Gene Swimmer and Mark Thompson.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Civil service; Collective bargaining; Labor Unions; Public sector; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z